Monitoring COVID-19 Impacts on Households in Ethiopia, Report No. 6 : Results from a High-Frequency Phone Survey of Households, Round 5 - Ambel, Alemayehu A. (World Bank, Washington, DC, 2020)
The Ethiopian high-frequency phone survey of households (HFPS-HH) allows for a better understanding of the effects of COVID-19 on households and provides data in almost real time to support new responses to the pandemic as they become necessary. The HFPS-HH builds on the national longitudinal Ethiopia Socioeconomic Survey (ESS) that the Central Statistics Agency (CSA) carried out in 2019 in collaboration with the World Bank. The HFPS-HH subsample of the ESS sample is representative of households with access to a phone. The survey began in April 2020 with respondents of 3,249 households in Round 1. The same households are tracked for six months, with selected respondents, typically household heads, completing phone-based interviews every three to four weeks. This one-pager summarizes the results of the fifth round of the HFPS-HH. This round took place about 5 months into the pandemic. In this round the survey interviewed 2,770 households in both urban and rural areas in all regions of Ethiopia, implemented between August 24 and September 17, 2020.